Strategic Model of Mental Health Nurse Competence and Caregiver in Preventing Relapse Risk in Schizophrenia Patients - M. Suhron; Sitti Sulaihah; Faisal Amir (Universitas STRADA Indonesia, 2026)
Background: The competences under consideration include clinical knowledge, clinical skills, communication competence, crisis and safety management, professional growth, management of care, and recommendations. Purpose: Analyzing the Strategic Model of Mental Health Nurse Competence and Caregiver in Preventing Relapse Risk in Schizophrenia Patients. Methods: The study used a quantitative design with a cross-sectional methodology and included 110 participants, including nurses and caregivers from five community health clinics in East Java Province. The data were obtained using a Likert-scale instrument that was previously validated and reliable. The data was analyzed using the Structural Equation Modeling (SEM) approach using the SmartPLS tool. Results: All competency characteristics of psychiatric nurses and caregivers have a substantial and essential relationship to the prevention of relapse risk in schizophrenia patients, with a very high model commitment in producing variations in variables which are dependent variables. Conclusion: Thoroughly enhancing the competence of psychiatric nurses and caregivers is an effective method for lowering relapse rates among schizophrenia patients. Suggestions include enhancing the psychiatric nurse education curriculum, providing competency-based continuing training, and incorporating collaborative care models into health care organizations.